Mechanical Vibrations - Rao, S. Singireus ([S.l.] : Verso, 1999)
Tariq Ali's second novel in The Islam Quintet is a rich and teeming chronicle set in twelfth-century Cairo, Damascus and Jerusalem. The Book of Saladin is the fictional memoir of Saladin, the Kurdish liberator of Jerusalem, as dictated to a Jewish scribe, Ibn Yakub. Saladin grants Ibn Yakub permission to talk to his wife and retainers so that he might present a full portrait in the Sultan's memoirs. A series of interconnected stories follows, tales brimming over with warmth, earthy humor and passions in which ideals clash with realities and dreams are confounded by desires. At the heart of the novel is an affecting love affair between the Sultan's favored wife, Jamila, and the beautiful Halina, a later addition to the harem. The novel charts the rise of Saladin as Sultan of Egypt and Syria and follows him as he prepares, in alliance with his Jewish and Christian subjects, to take Jerusalem back from the Crusaders. This is a medieval story, but much of it will be uncannily familiar to those who follow events in contemporary Cairo, Damascus, and Baghdad. Betrayed hopes, disillusioned soldiers and unrealistic alliances form the backdrop to The Book of Saladin .